2023
DOI: 10.1002/bio.4483
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of efficient photoconduction and enhanced luminescence characteristics of Ce‐doped ZnO nanophosphors for UV sensors

Abstract: This study involves the single-step, mass-scale productive synthesis, photoconduction, and luminescence characteristics of pure and cerium rare-earth-ion-doped ZnO (CZO) nanophosphors with different Ce concentrations (Ce: 0, 2, 4, 6, and 8 wt.%) synthesized using the solid-state reaction method. The synthesized nanophosphors were characterized for their structural, morphological, optical, and photoconductivity (PC) properties using X-ray diffraction (XRD), field-effect scanning electron microscopy (FE-SEM), en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The study's results suggested that the fabricated sensor was highly selective and sensitive towards UA. Kumar et al [53] fabricated Ce‐doped zinc oxide (CZO) nanophosphors at varied cerium ion concentrations. The diffraction peak intensities in CZO were reduced with increased dopant concentrations, which indicated that an increase in cerium concentration affected the zinc oxide crystal structure, whereas, in the pure sample, the presence of sharp peaks showed high crystallization.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…The study's results suggested that the fabricated sensor was highly selective and sensitive towards UA. Kumar et al [53] fabricated Ce‐doped zinc oxide (CZO) nanophosphors at varied cerium ion concentrations. The diffraction peak intensities in CZO were reduced with increased dopant concentrations, which indicated that an increase in cerium concentration affected the zinc oxide crystal structure, whereas, in the pure sample, the presence of sharp peaks showed high crystallization.…”
Section: Overview Of Published Researchmentioning
confidence: 99%